Use of NVivo in Complaint Analysis About Hospital Services to Improve Customer Satisfaction - Posma Sariguna Johnson Kennedy (International Journal of Artificial Intelligence Research, 2022)
The development of qualitative research must balance the ability to use computers to facilitate data analysis. We created this study for this purpose. NVivo is used to analyze complaints from users at the Dharmais Cancer Hospital, Jakarta. This study is intended to collect data in the real-world context of hospitals regarding customer service through. NVivo was very helpful in processing data and analyzing various information from all informants. The customer's expectation is an integrated service, starting from the time of diagnosis to planning and preparing for continuous care that is effective and efficient, so as to save health expenses.